Effect of foliar application of plant growth regulators on growth, yield and post harvest losses of potato (Solanum tuberosum) - W, BIRBAL; SINGH, R K; KUMAR, VINOD; KUSHWAH, V S (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted during the winter (rabi) season of 2002 and 2003 to find out the suitable plant growth regulators for foliar spray to maximize seed potato yield. A total of 7 treatments including control were tested in randomized block design with 3 replications on ‘Kufri Ashoka’ potato (Solanum tuberosum L). The results indicated that plant growth regulators, like GA3, NAA, TIBA and ethrel significantly increased seed size (25–75 g) tubers yield as well as total tuber yield. Significantly maximum total tuber yield (37.0 tonnes/ha) was achieved with GA3 @ 200 ppm treatment, followed by ethrel (35.0 tonnes/ha) in comparison to control (30.4 tonnes/ha). The multiplication rate also varied from 12.8 to 14.6 with different plant growth regulators.The minimum rottage losses were observed with NAA treatment when tubers were kept for short-term storage after harvest at ambient conditions. At the end of the storage, significant dry matter increase was also observed with treatments ethrel, TIBA and NAA.